2015
DOI: 10.1590/s0036-46652015000500016
|View full text |Cite
|
Sign up to set email alerts
|

FIRST REPORT OF CUTANEOUS LEISHMANIASIS CAUSED BY Leishmania (Leishmania) infantum chagasi IN AN URBAN AREA OF RIO DE JANEIRO, BRAZIL

Abstract: SUMMARYAmerican tegumentary leishmaniasis (ATL) is an infectious disease caused by protozoa of the genus Leishmania, and transmitted by sandflies. In the state of Rio de Janeiro, almost all of the cases of American tegumentary leishmaniasis (ATL) are caused by Leishmania (Viannia) braziliensis, while cases of visceral leishmaniasis (VL) are caused by Leishmania (Leishmania) infantum chagasi. The resurgence of autochthonous VL cases in Rio de Janeiro is related to the geographic expansion of the vector Lutzomyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
0
21
1
9
Order By: Relevance
“…These lesions ulcerate, evolve over time and do not present a hypopigmented halo . These characteristics differ from the data presented in our study and by other authors regarding the disease observed in Central America where the lesions do not ulcerate regardless of the evolution time and are often surrounded by a hypopigmented halo . In both South America and Central America, patients do not have a previous history of VL.…”
Section: Discussioncontrasting
confidence: 99%
“…These lesions ulcerate, evolve over time and do not present a hypopigmented halo . These characteristics differ from the data presented in our study and by other authors regarding the disease observed in Central America where the lesions do not ulcerate regardless of the evolution time and are often surrounded by a hypopigmented halo . In both South America and Central America, patients do not have a previous history of VL.…”
Section: Discussioncontrasting
confidence: 99%
“…L. infantum is phylogenetically close to Leishmania donovani, the agent that causes VL and post-kala-azar dermal leishmaniasis in the Old World (Europe); 17 occurrence of cutaneous lesions caused by L. infantum in immunocompetent individuals is uncommon in the Americas, especially in Brazil. 14,18 L. infantum has been isolated in the skin of Africans with CL, producing a lesion histologically distinct from that caused by L. major. 19 Since 2015, cases of CL caused by L. infantum have been recorded in different Brazilian states.…”
Section: Discussionmentioning
confidence: 99%
“…19 Since 2015, cases of CL caused by L. infantum have been recorded in different Brazilian states. 14,18 In Africa and the Americas, the clinical characteristics of CL vary according to the etiological agent. 1,19 Our study highlights the pleomorphism of CL caused by L. infantum, alerting a) Molecular diagnosis based on polymerase chain reaction (PCR) and Leishmania hsp70-234 gene region sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Adult infection rates are increasing while those in children have decreased [23], probably due to improvements in nutrition and immunization rates for other diseases. Atypical cutaneous leishmaniasis caused by L. infantum has also been described in the country [24,25]. In such circumstances, the diagnosis based strictly on visual inspection of clinical signs lacking proper Leishmania species identification leads to the misassumption of a low risk of VL in the region, further complicating the management of the spread of the parasite and challenging disease surveillance and control.…”
Section: Introductionmentioning
confidence: 99%